Pengelolaan Bisnis Berbasis Digital pada Usaha Mikro “Dapur Umma” di Era New Normal - Qristin Violinda; Noni Setyorini; Ika Indriasari; Ira Setiawati (Universitas Muhammadiyah Semarang, 2022)
Dapur Umma is a micro business in the culinary field that produces various bottled chili sauce, dried potatoes and spring rolls and fireworks. Based on the results of the field survey, it was found that Dapur Umma had limited problems in marketing its products to the public during the Covid-19 pandemic, where the number of requests that usually came from outside the city fell by up to 60%. This is a problem that cannot be found for a solution because (1) the lack of knowledge about how to promote their products digitally which is interesting and unique and has durability (2) Limited knowledge in financial management to be able to calculate the profit value of the sale of Umma Kitchen. This Community Partnership Program (PKM) aims to help the Umma Kitchen Micro Business which is engaged in the business of chili sauce, dried potatoes and firecracker spring rolls to be able to increase sales value through digital-based marketing and financial management techniques solutions. The final result of this activity can increase the production and marketing value from 45% to 85%.